Mesolevel Analysis of Hydrodynamics of Flow Over Hydrophobic Surfaces. (2016) - Jose, Jubin V.; Kamath, Pradeep M.
Abstract: In this study, hydrodynamics of flow over a super-hydrophobic surface was investigated using Lattice Boltzmann method. Lattice Boltzmann method is a meso-level approach, to capture the mico-level details in the flow regime. From the numerical analysis it was found that, an effective mixing was induced in the flow domain with the introduction of hydrophobic surfaces in the channel. The cross stream velocity fields induced potentially proves its capability to create induced mixing in the channel. The result was found to be in fine agreement with the results in the literature. The exceptional capability of reducing the pumping power makes this modification more acceptable.